Analisis Tipe Fluida Manifestasi Panas Bumi Daerah Mata Air Panas Sungai Kepangian Desa Sawangan Kabupaten Minahasa Utara - Risma P. Sambolayuk; Rolles Nixon Palilingan; Jeferson Polii; Donny Royke Wenas (Fakultas Matematika Ilmu Pengetahuan Alam dan Kebumian, Universitas Negeri Manado, 2024)
Geothermal is a source of heat energy contained in hot water, rocks, water vapor as well as gases and minerals and others that cannot be genetically separated from a geothermal system. Geothermal energy is a renewable natural resource with high potential. The source of this energy comes from heating magma against water rocks together with elements contained in the earth's crust. North Sulawesi has the potential to become a geothermal development area, both directly and indirectly. The existence of hot springs shows that the research location in Sawangan Village has geothermal potential. This research aims to determine the fluid type and molecular functional groups of hot springs in Sawangan Village, North Minahasa Regency, North Sulawesi Province. Using geochemical methods using Cl-SO2-HCO3 and FTIR diagrams, it is known that the type of hot spring fluid in Sawangan Village is Bicarbonate (HCO3) and the molecular functional group is C=O, where the parent chain C binds HCO3 (Bicarbonate) which corresponds to fluid type results.